Construction of Coated Selective Electrode with Copper Oxide Nanoparticles and its Comparison with the Conventional Selective Electrode for Determination of Cyproheptadine Hydrochloride (Journal of Pharmaceutical Negative Results, 2022)
The tremendous advances in nanoscience and nanomaterials have witnessed great success for nanoparticles due to their unique properties, vastly diverse fields, uses, and electrical activity. Scientific researchers in the different and multifunctional activities of nanoparticles prompted to give great attention to these nanoparticles as materials of great usefulness and effective in electrochemical applicationsas well as for sensing. This study calculated the potential difference after two electrodes were made to estimate the antihistamine drug cyproheptadine hydrochloride (CPH). One is the conventional coated wire electrode and the other is the wire electrode enriched withCuONPs (modified electrode). The results show that the linear range of the conventional selective electrode (I) is range of (10-2 - 10-7) mol/L, while the linear range of the nanoselective electrode (II) is range of (10-2 - 10-8) mol/L, The slope of the conventional and nano-electrode enriched with nanoparticles (I, II) is (56.057, 58.143) mV/decade, respectively. We note that the estimation coefficients for the manufactured electrodes (II, I) are (0.9990, 0.9987) consecutively. These results found that the electrode enriched with nanoparticles (modified) is more sensitive and selective and has an advantage over the traditional selective electrode. Its advantage in electrical improvement enabled it to quickly perform the search for the drug under study (CPH) with wide concentration ranges and low limits, in addition to the speed of electrode sensing.